Developing Poster as Media in Teaching Reading Comprehension of Descriptive Text - Ketrein Triyas Mayaneta; Alimin Alimin; Happy Kusuma Wardani (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
For students in senior high school, especially in the tenth grade, reading comprehension is usually taught in English language learning. Based on this, research on the development of posters as a learning media in teaching reading is very necessary because the presence of attractive media can attract an interest in reading and create a productive learning process. The purpose of this research is to develop posters as a media in teaching reading comprehension of descriptive text for the tenth graders of SMK NU 2 Soko. This research design is Research and Development (R&D) using the ADDIE model. This model consists of five stages. These stages are analysis, design, development, implementation, and evaluation. The data collected was analyzed qualitatively. The instruments used during the need analysis were questionnaires, interviews, and at the implementation stage using observation sheets and field notes. In addition, questionnaires were distributed to English teacher and students to find out their responses and opinion about the products that are developed at the evaluation stage. The result of this research is a poster as a learning media for tenth graders. The poster is made based on the results of the needs analysis and input from expert validators and English teacher. The poster consists of three themes (tourism, restaurant, hotel). on the first sheet and the second sheet contains vocabulary building and 20 questions. The developed poster received good responses and attention.This proves that the use of poster as learning media has been well received by students and makes a significant positive contribution to the reading learning process of the tenth graders at SMK NU 2 Soko.